Theoretical Analysis of Feeling Loneliness (Eurasian Scientific Herald, 2023)
The feeling of loneliness is a socio-psychological phenomenon, the analysis of which requires the study of surreal theoretical approaches. Each approach, as well as the ideas and opinions that scientists have put forward on this issue, consists of colorfulness. This article is aimed at highlighting the content and essence of the feeling of loneliness on the basis of theoretical analysis. It is envisaged that the relationship of the feeling of loneliness with the aggressive behavior will be revealed. Also it takes a review of the ideas of S.G.Korchagina on the problem of loneliness and made some theoretically deductions.